ERP ??? Enterprise Resource Planing : "como escolher o melhor para uma empresa" - Paulo, Wagner Carreira (2002)
The stability of the Brazilian economy, initiated in the 90s, allied to the process of globalization, compelled companies to be more competitive in order to face the challenges of the new world order. Investment in new technologies was one way to achieve modernization. The Brazilian market, as well as the world market, owns state-of-the-art technologies. Whenever these technologies are well selected and employed, they help the organizations to attain their strategic goals. The aim of this study is to systematize information on the validation and process of choice of Integrated Management Systems named ERP ??? Enterprise Resource Planning. Based on the author???s professional experience, on information raised next to specialists and on bibliographical review, it was verified that those systems attend to the standards of excellence of the National Quality Award and that the process of choice has to be led by a Project Team able to prioritize the essential or strategic functionalities of the enterprise. The Business Management Systems are not a solution by themselves. As in relation to any tool, their users need to know their potential in order to get the better of them. We try to prove that the responsibility for the success of the utilization of an ERP depends on the organization, represented by the collaborators responsible for the implementation of the product, and not on the supplier. When the activities of each stage of the project, as the ones of selection and implementation of an ERP, are professionally and responsibly performed, success is the end product.